2008
DOI: 10.1017/s0025315408000842
|View full text |Cite
|
Sign up to set email alerts
|

Polydorid species (Polychaeta: Spionidae) in south-western Australian waters with special reference to Polydora uncinata and Boccardia knoxi

Abstract: Eight species of polydorid polychaetes were found to inhabit mollusc shells from south-western Australian waters. Numerous individuals of Polydora uncinata were extracted for the first time from the shells of both land-based cultured abalone Haliotis laevigata and H. roei, as well as from natural subtidal H. roei and Chlamys australis. Shells of the oyster Saccostrea commercialis cultured in sea-based systems were infested by Boccardia knoxi which was first recorded in these waters. Polydora aura, Dipolydora g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…Similarly, many polydorid species (in cluding non-indigenous and pest species) have been recorded in South Africa (14; e.g. Boonzaaier et al 2014, Williams 2015, Australia (9; Blake & Kudenov 1978, Skeel 1979, Sato-Okoshi et al 2008, Walker 2014Handley & Bergquist 1997, Read & Handley 2004, Read 2010), Chile (6; Sato-Okoshi & Takatsuka 2001, Moreno et al 2006) and Brazil (5; Radashevsky et al 2006). In contrast, only 4 polydorid species have been re corded in China, on 5 hosts (Zhou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, many polydorid species (in cluding non-indigenous and pest species) have been recorded in South Africa (14; e.g. Boonzaaier et al 2014, Williams 2015, Australia (9; Blake & Kudenov 1978, Skeel 1979, Sato-Okoshi et al 2008, Walker 2014Handley & Bergquist 1997, Read & Handley 2004, Read 2010), Chile (6; Sato-Okoshi & Takatsuka 2001, Moreno et al 2006) and Brazil (5; Radashevsky et al 2006). In contrast, only 4 polydorid species have been re corded in China, on 5 hosts (Zhou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation in on-shore systems of species producing larvae which emerge at a late stage of development may be a consequence of local recruitment of larvae settling soon after emergence from Wilson 1928, Read 1975, Lleonart 2001, Sato-Okoshi 1998, 1999, Sato-Okoshi et al 2008, were identified as important pests in 5 off-shore systems. In at least 3 of these instances the hosts did not develop from natural spatfall and had been transported from nursery systems (Lleonart et al 2003, Simon 2015.…”
Section: Adelphophagymentioning
confidence: 99%
See 3 more Smart Citations